2017
DOI: 10.1155/2017/7409420
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of Potential Skin Penetration-Enhancers Using Stratum Corneum Lipid Liposomes: Preliminary Evaluation for Different Concentrations of Ethanol

Abstract: In this study, we developed a technique for high-throughput screening (HTS) of skin penetration-enhancers using stratum corneum lipid liposomes (SCLLs). A fluorescent marker, sodium fluorescein (FL), entrapped in SCLLs was prepared to provide a preliminary evaluation of the effect of different concentrations of ethanol on the disruption effect of SCLLs, which is an alternative for skin penetration-enhancing effects. In addition, SCLLs containing a fluorescent probe (DPH, TMA-DPH, or ANS) were also prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Furthermore, it was found in our present work that the effect of CPEs on FL leakage and SCLL fluidity were dependent on the CPE concentration. 21) Similarly, in the study by Suhonen et al, 18) calcein leakage from SCLLs was concentration dependent for 1-dodecanol and concave downwards for Azone and dodecyl-2-(N,N-dimethylamino)propionate (DDAIP). Kim et al 15) also observed that the lipid phase transition temperature of SCLLs shifted progressively towards lower temperature with the increased concentration of pyrrolidone derivatives.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, it was found in our present work that the effect of CPEs on FL leakage and SCLL fluidity were dependent on the CPE concentration. 21) Similarly, in the study by Suhonen et al, 18) calcein leakage from SCLLs was concentration dependent for 1-dodecanol and concave downwards for Azone and dodecyl-2-(N,N-dimethylamino)propionate (DDAIP). Kim et al 15) also observed that the lipid phase transition temperature of SCLLs shifted progressively towards lower temperature with the increased concentration of pyrrolidone derivatives.…”
Section: Discussionmentioning
confidence: 83%
“…21) Similarly, Yoneto et al 17) found a good correlation between the enhancement of sugar molecule release from SCLLs and the enhancement factor on the lipoidal pathway of hairless rat SC in the presence of pyrrolidone derivatives. Furthermore, it was found in our present work that the effect of CPEs on FL leakage and SCLL fluidity were dependent on the CPE concentration.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was shown that the ux of the drug increased with increase in ethanol concentration up to 80% ethanol volume fraction. Sakdiset et al 46 carried out permeation experiments of caffeine through skin in presence of various concentrations of ethanol aqueous solution. The enhancement ratio of caffeine ux increased $4 times with ethanol concentration of x ¼ 0.1 to x ¼ 0.7.…”
Section: Permeation Of Drug Molecule In Presence Of Ethanolmentioning
confidence: 99%
“…To overcome the barrier function of the SC, CPEs are conventional and effective approaches as they reduce skin barrier resistance and thus promote the penetration of drugs [20,21].…”
Section: Chemical Penetration Enhancersmentioning
confidence: 99%